2016
DOI: 10.1007/s00223-016-0155-1
|View full text |Cite
|
Sign up to set email alerts
|

Sonic Hedgehog Promotes Cementoblastic Differentiation via Activating the BMP Pathways

Abstract: Although sonic hedgehog (SHH), an essential molecule in embryogenesis and organogenesis, stimulates proliferation of human periodontal ligament (PDL) stem cells, the effects of recombinant human SHH (rh-SHH) on osteoblastic differentiation are unclear. To reveal the role of SHH in periodontal regeneration, expression of SHH in mouse periodontal tissues and its effects on the osteoblastic/cementoblastic differentiation in human cementoblasts were investigated. SHH is immunolocalized to differentiating cementobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 62 publications
(86 reference statements)
1
18
0
Order By: Relevance
“…Previously, the BMP/Smad and Akt/MAPK/NF-κB pathways were found to contribute to rh-SHH-induced osteoblastic or cementoblastic differentiation [23], and a stepwise pathway involving Akt/JNK or Akt-MAPK/ERK was demonstrated to regulate cell inflammation, an undifferentiated state and viability [25,59]. These findings are consistent with our data that JNK activation induced by M2 Mφs was inhibited by the addition of Akt inhibitor (Fig.…”
Section: Stem Cellssupporting
confidence: 93%
See 1 more Smart Citation
“…Previously, the BMP/Smad and Akt/MAPK/NF-κB pathways were found to contribute to rh-SHH-induced osteoblastic or cementoblastic differentiation [23], and a stepwise pathway involving Akt/JNK or Akt-MAPK/ERK was demonstrated to regulate cell inflammation, an undifferentiated state and viability [25,59]. These findings are consistent with our data that JNK activation induced by M2 Mφs was inhibited by the addition of Akt inhibitor (Fig.…”
Section: Stem Cellssupporting
confidence: 93%
“…Given that the Wnt/β-catenin, Akt, TGF-β/Smad, BMP/Smad, and MAPK pathways have been demonstrated to regulate the osteogenesis/cementogenesis process [20][21][22][23][24][25][26][27][28], key genes involved in the above pathways were selected to screen the potential pathways that regulate M2 Mφ-enhanced cementoblastic differentiation. When the expression of the selected genes in CM-M2-treated PDLSCs (M2 group) and untreated PDLSCs (Control group) was analyzed using qRT-PCR, the pathway-related genes that were differentially expressed between the two groups were plotted in a heatmap (Fig.…”
Section: Potential Pathways Involved In M2 Mφ-enhanced Cementoblasticmentioning
confidence: 99%
“…Recent studies have demonstrated that growth factors, including BMPs and transforming growth factor-beta, mediate reciprocal epithelial-mesenchymal interactions during tooth root development [21,45,46,59]. It has also been shown that the epithelial cells of the HERS secrete Shh [42,43,60]. In this process, via Shh signaling, dental mesenchymal cells expressing Ptch are stimulated to form the root dentin [35,36].…”
Section: Deletion Of Shh Signaling In Hertwig's Epithelial Root Sheatmentioning
confidence: 99%
“…ERK‐1/2 are widely investigated as key regulators in bone formation . Recent researches showed that they are important intermediary signaling molecules for cementoblastic differentiation and cementogenesis . Inhibition of ERK1/2 phosphorylation downregulated the expression of cementum attachment protein and cementum protein‐1 .…”
Section: Introductionmentioning
confidence: 99%